A network meta-analysis of the effect of physical exercise on core symptoms in patients with autism spectrum disorders - Li, Lili; Jia, Shuqi; Wang, Peng; Li, Shufan; Wang, Xing; Zhu, Xiaoyi (Frontiers in Neurology, 2024)
Objective: To compare the effects of various sports exercise programs on the core symptoms of patients with Autism Spectrum Disorder (ASD). Methods: We searched the China National Knowledge Infrastructure, VIP databases, Wanfang databases, Cochrane Library, PubMed, EMBASE, and Web of Science databases from their inception to February 2023 for randomized controlled trial that investigated the effect of sports exercise on the core symptoms of ASD. The overall risk of bias in the included literature was summarized using the revised Cochrane Randomised Trial Risk of Bias Tool (ROB2), and network meta-analysis was used to compare the intervention effects. Results: A total of 30 studies involving 1375 participants were included. The results showed that sports exercise programs, including 8-12 weeks of ball sports (SMD=-5.35, 95%CI: -7.57, -3.23), horse riding (SMD=-3.71, 95%CI: -6.18, -1.13), 8-12 weeks of comprehensive sports exercise (SMD=-2.17, 95%CI: -3.99, -0.44), and more than 12 weeks of comprehensive sports exercise (SMD=-3.75, 95%CI: -6.33, -1.24), significantly improved social interaction disorders. Furthermore, 8-12 weeks of ball sports 95%CI: 2.04, 6.73) and more than 12 weeks of comprehensive sports exercise (SMD=3.65,95%CI:1.40,6.08) significantly improved repetitive behaviors and restricted interests. Conclusion: Sports exercise can improve the core symptoms of ASD patients, and different symptoms show a selective response to different exercise elements.